Recycled brick masonry aggregate in hollow section beam - Norjan, Arasat (2014)
This study is about using of recycled aggregates in reinforced hollow section concrete beam. Hollow section structures are widely used because it can help reduce the structure self weight and costs. Nowadays, the increases of demolition wastes have become serious in environmental problem and cause unpleasant view especially in urban area. Due to concerns in environmental safety and the increase in aggregate demand, the industry field is success to acknowledge recycle aggregate which is from the construction and demolition aggregate. In this study the recycled crushed brick aggregate is used as a replacement of coarse aggregate in concrete design. This study was conducted to determine the flexural strength and the best effect of cavity size in reinforced hollow section beam. This study includes, materials preparation, mixing and curing, and filling concrete to formwork. Beam concrete undergo curing process by using wet gunny curing for 28 days. After curing beam was test by using Magnus frame to know the flexural strength. Based on this study beam sample with cavity size 50mm x 100mm shows the highest ultimate loading 137.95kN followed by beam sample with cavity size 40mm x 100mm. While, beam sample with cavity size 60mm x 100mm shows the ultimate strength 136.34kN. Besides that, beam sample with cavity size 50mm x 100mm has the best effect to enhance the beam strength. This beam showed lower deflection for the same loading on each sample. From these result it shown that normal and reasonable strength concrete can produced using recycled aggregate. The replacement of natural aggregate with recycled aggregate can enhance the concrete performance to meet the industry needs.